PENINGKATAN KEMAMPUAN BELAJAR PERDAGANGAN INTERNASIONAL DENGAN TEKA-TEKI EKONOMI PADA SISWA KELAS XI-IPS - Ani, Risa Ari (Dinamika Pendidikan, 2014)
The materials of international trade are full of economic theories and terms which make students difficult to understand the materials, so it needs a medium to facilitate students in learning. The purpose of this study was to determine the use of Economics Puzzle learning media to improve studentsâ€™ understanding of open economy material. It was a Class Action Research with 2 cycles done in SMA N 1 Mranggen at the 2nd semester of the academic year 2013/2014. The subjects of the study were 31 students of class XI IPS 2. The results showed that the average of studentsâ€™ learning outcomes was 73 on the 1st cycle and increased up to 76 on the 2nd cycle. The classical achievement also increased from 87% on the 1st cycle up to 94% on the 2nd cycle.Â